Sello Aerobic Gymnastics Mode (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The main object of the study is to create a model of low aerobic impact, which is called the â€œSello Aerobic Gymnastics Model.â€ The product of this study is video has packaged in a VCD (Video Cassette Disc). This study uses a research design by Borg and Gall, Research and Development (R & D). The subjects of this study are level 2 of physical education student STKIP Kusumanegara Jakarta. In the effectiveness test by this has tvalue is smaller than ttable, namely 13.54 and 1.86 and Ha is accepted, meaning that the Sello Aerobic Gymnastics Model is feasible to be applied in the small group tryout and field group tryout. Conclusion of this study are Sello Aerobic Gymnastics Model can be used as a physical education student preparation in Field Experience Program (Program Pengalaman Lapangan/PPL) so that students have the provision to be applied aerobic skill and brought to school, Sello Aerobic Gymnastics Model has given new atmosphere and new gymnastics references that are suitable for beginners as a motivation and introduction of aerobics for level 1. By the results of the small group tryout, and the field group tryout can be concluded that Sello Aerobic Gymnastics Model can improve aerobic skill for physical education student.